2013
DOI: 10.1038/npp.2013.103
|View full text |Cite
|
Sign up to set email alerts
|

D-Amino Acid Aberrations in Cerebrospinal Fluid and Plasma of Smokers

Abstract: The glutamatergic neurotransmission system and the N-methyl-D-aspartate receptor (NMDAR) have been implicated in smoking and alcohol consumption behavior. Preclinical studies have demonstrated that nicotine and ethanol influence NMDAR functionality, which may have a role in tendencies to consume these substances. Nonetheless, little is known about concentrations of NMDAR coagonists in the cerebrospinal fluid (CSF) and plasma of individuals who smoke or consume alcohol. Glycine and L-and D-stereoisomers of alan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The first participant was recruited before July 2008, and plasma and CSF were collected preceding the administration of spinal anesthesia for minor elective surgery at different hospitals in and near Utrecht, Netherlands, between July 2008 and November 2011. Subject characteristics and details of sample collection were described previously (38)(39)(40). In summary, subjects were included if they were of North-Western European descent (ie, all grandparents born in the Netherlands, Belgium, France, Germany, Denmark, or the United Kingdom).…”
Section: Subjects and Sample Collectionmentioning
confidence: 99%
“…The first participant was recruited before July 2008, and plasma and CSF were collected preceding the administration of spinal anesthesia for minor elective surgery at different hospitals in and near Utrecht, Netherlands, between July 2008 and November 2011. Subject characteristics and details of sample collection were described previously (38)(39)(40). In summary, subjects were included if they were of North-Western European descent (ie, all grandparents born in the Netherlands, Belgium, France, Germany, Denmark, or the United Kingdom).…”
Section: Subjects and Sample Collectionmentioning
confidence: 99%
“…In humans, AAs most commonly occur in their l‐ form, but there is increasing evidence that d‐ AAs also play essential roles in human biology. d‐ AAs are involved in the pathogenesis of psychiatric disease and abnormal levels were found in human disorders, such as schizophrenia and Alzheimer's disease . In the aforementioned applications, the AA enantiomers often are minor components of complex mixtures, such as biological fluids and food, requiring the use of highly selective separation and detection techniques for their unambiguous assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is often more common in patients groups than among HC (e.g. Jakobsson et al (33)) and smoking status has previously been associated with CSF biomarker levels of amino acids in CSF (51). However, Pålsson et al found that adding smoking as a co-variate did not explain observed differences between BD and HC for glutamate markers (41).…”
Section: ) Smokingmentioning
confidence: 99%